Possibilities and challenges of small molecule organic compounds for the treatment of repeat diseases - NAKATANI, Kazuhiko (Proceedings of the Japan Academy, Series B, 2022)
The instability of repeat sequences in the human genome results in the onset of many neurological diseases if the repeats expand above a certain threshold. The transcripts containing long repeats sequester RNA binding proteins. The mechanism of repeat instability involves metastable slip-out hairpin DNA structures. Synthetic organic chemists have focused on the development of small organic molecules targeting repeat DNA and RNA sequences to treat neurological diseases with repeat-binding molecules. Our laboratory has studied a series of small molecules binding to mismatched base pairs and found molecules capable of binding CAG repeat DNA, which causes Huntington’s disease upon expansion, CUG repeat RNA, a typical toxic RNA causing myotonic dystrophy type 1, and UGGAA repeat RNA causing spinocerebellar ataxia type 31. These molecules exhibited significant beneficial effects on disease models in vivo, suggesting the possibilities for small molecules as drugs for treating these neurological diseases.